2022
DOI: 10.1590/1413-82712022270101
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Children with Cancer: Relapse and Survival Perspectives

Abstract: In Brazil, few studies have investigated the psychological aspects of childhood cancer. The aim of this article was to compare the psychological adjustment of children with cancer from different survival perspectives with that of children without cancer, besides examining potential risk factors. The sample consisted of 179 participants (6-14 years-old) recruited in two Brazilian public hospitals and three schools, and divided in three groups (relapsed, survivors and control). Children answered orally the self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Wechsler et al 36 reported good psychological adaptation of Brazilian CCSs. Nikolskaya et al 37 validated the Russian version of the Distress Rating Scale.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Wechsler et al 36 reported good psychological adaptation of Brazilian CCSs. Nikolskaya et al 37 validated the Russian version of the Distress Rating Scale.…”
Section: Discussionmentioning
confidence: 98%
“…used a self‐designed survey and reported no difference in mental health concerns amongst a CCS cohort in India and their siblings. Wechsler et al 36 . reported good psychological adaptation of Brazilian CCSs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations